Progressive Seizure Aggravation in the Repeated 6-Hz Corneal Stimulation Model Is Accompanied by Marked Increase in Hippocampal p-ERK1/2 Immunoreactivity in Neurons - Giordano, Carmela; Costa, Anna M.; Lucchi, Chiara; Leo, Giuseppina; Brunel, Luc; Fehrentz, Jean-Alain; Martinez, Jean; Torsello, Antonio; Biagini, Giuseppe (Frontiers in Cellular Neuroscience, 2016)
The 6-Hz corneal stimulation test is used to screen novel antiepileptic molecules to overcome the problem of drug refractoriness. Although recognized as a standard test, it has been evaluated only recently in the attempt to characterize the putative neuronal networks involved in seizures caused by corneal stimulation. In particular, by recording from the CA1 region we previously established that the hippocampus participates to propagation of seizure activity. However, these findings were not corroborated by using markers of neuronal activation such as FosB/ΔFosB antigens. In view of this discrepancy, we performed new experiments to characterize the changes in levels of phosphorylated extracellular signal-regulated kinases1/2 (p-ERK1/2), which are also used as markers of neuronal activation. To this aim, mice underwent corneal stimulation up to three different times, in three sessions separated by an interval of three days. To characterize a group in which seizures could be prevented by pharmacological treatment, we also considered pretreatment with the ghrelin receptor antagonist EP-80317 (330 µg/kg). Control mice were sham-treated. Video electrocorticographic recordings were obtained from mice belonging to each group of treatment. Animals were finally used to characterize the immunoreactivity for FosB/ΔFosB and p-ERK1/2 in the hippocampus. As previously shown, FosB/ΔFosB levels were highly increased throughout the hippocampus by the first induced seizure but, in spite of the progressively increased seizure severity, they were restored to control levels after the third stimulation. At variance, corneal stimulation caused a progressive increase in p-ERK1/2 immunoreactivity all over the hippocampus, especially in CA1, peaking in the third session. Predictably, EP-80317 administration reduced both duration and severity of seizures, prevented the increase in FosB/ΔFosB levels in the first session, and partially counteracted the increase in p-ERK1/2 levels in the third session. The vast majority of p-ERK1/2 immunopositive cells were co-labeled with FosB/ΔFosB antibodies, suggesting the existence of a relationship between the investigated markers in a subpopulation of neurons activated by seizures. These findings suggest that p-ERK1/2 are useful markers to define the aggravation of seizures and the response to anticonvulsant treatments. In particular, p-ERK1/2 expression clearly identified the involvement of hippocampal regions during seizure aggravation in the 6-Hz model.